Implementation of the Building Permit Issuance Policy in Bontang City - Rizal Mutadi; Aji Ratna Kusuma; Daryono Daryono (Journal of Government and Politics (JGOP), 2025)
This study examines the implementation of the building permit policy in Bontang City, focusing on the dynamics of administrative procedures, institutional coordination, and stakeholder compliance in urban governance. Using a qualitative research method, data were collected through interviews, document analysis, and field observations to explore the challenges and interactions among local government agencies, developers, contractors, and community representatives. The findings reveal that while the regulatory framework for building permit issuance is clearly defined, its practical implementation faces obstacles such as bureaucratic inefficiency, overlapping authority, and varying stakeholder capacities. Institutional coordination and stakeholder engagement play a crucial role in ensuring compliance and effective policy enforcement. The study concludes that enhancing administrative efficiency, strengthening inter-agency collaboration, and providing support for smaller stakeholders are essential strategies for improving regulatory compliance and promoting sustainable urban development in Bontang City.